If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -315h + 23 + -17 = 11h + 984 Reorder the terms: 23 + -17 + -315h = 11h + 984 Combine like terms: 23 + -17 = 6 6 + -315h = 11h + 984 Reorder the terms: 6 + -315h = 984 + 11h Solving 6 + -315h = 984 + 11h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-11h' to each side of the equation. 6 + -315h + -11h = 984 + 11h + -11h Combine like terms: -315h + -11h = -326h 6 + -326h = 984 + 11h + -11h Combine like terms: 11h + -11h = 0 6 + -326h = 984 + 0 6 + -326h = 984 Add '-6' to each side of the equation. 6 + -6 + -326h = 984 + -6 Combine like terms: 6 + -6 = 0 0 + -326h = 984 + -6 -326h = 984 + -6 Combine like terms: 984 + -6 = 978 -326h = 978 Divide each side by '-326'. h = -3 Simplifying h = -3
| -2.96+13d=13.2d | | 11(k-1)=7(k+2) | | 0.03+5.6f=8.38-11.1f | | 2x+8=5x-8+7-3x | | 6b+3c=27 | | 2x-4x+9=-2+5 | | -6(z-6)=-70 | | 9h=10.1h+18.26 | | 19.62+9.9y=-13.05+8y-0.8y | | 2x^2+xy+y^2=7 | | 3b+2k=16 | | 6x-1=2(x-5) | | 12+12=60 | | 7x+7(6x+17)=-322 | | 1.5d+7.75=1+2.25d | | 9-2p=-12-5p | | 18m+3n=84 | | X+.75x=120 | | 48-4x=88-9x | | 17+6b=-17b-16-13 | | 6m+5n=44 | | 2ln^2-3lnx-2=0 | | -3.7+1.91=-3.8r+0.51 | | 15a+3b=114 | | C=1.25p+5 | | 2x+3+3x=2+5x+1 | | 11c=2+8 | | -18j=-3-17j | | -q-16-5q=-9q+14 | | 42=x+3(2x+1) | | 28+1x=52+-7x | | 2.5x+4.5y=45 |